2009
DOI: 10.1089/rej.2009.0902
|View full text |Cite
|
Sign up to set email alerts
|

Forty Percent Methionine Restriction Decreases Mitochondrial Oxygen Radical Production and Leak at Complex I During Forward Electron Flow and Lowers Oxidative Damage to Proteins and Mitochondrial DNA in Rat Kidney and Brain Mitochondria

Abstract: Eighty percent dietary methionine restriction (MetR) in rodents (without calorie restriction), like dietary restriction (DR), increases maximum longevity and strongly decreases mitochondrial reactive oxygen species (ROS) production and oxidative stress. Eighty percent MetR also lowers the degree of membrane fatty acid unsaturation in rat liver. Mitochondrial ROS generation and the degree of fatty acid unsaturation are the only two known factors linking oxidative stress with longevity in vertebrates. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 71 publications
4
61
0
2
Order By: Relevance
“…With reference to the effect of MetR on mtROS generation and oxidative stress, it have been found that 80% MetR (without CR), as well as 40% MetR (Caro et al 2008(Caro et al , 2009, also decreases mtROS generation (mainly at complex I), % free radical leak, mtDNA oxidation, complex I content, specific markers of protein oxidative modification, and membrane unsaturation, in rat heart and liver mitochondria (Sanz et al 2006a, b, c, d), as well as rat kidney and brain mitochondria (Caro et al 2008(Caro et al , 2009, and that these decreases were dose-dependent and stronger at 80% than 40% MetR (Sanz et al 2006a, b, c, d;Caro et al 2008Caro et al , 2009. Strikingly, the pattern of many of these changes was very similar to those previously found in CR and PR.…”
Section: Oxidative Stress and Longevity From The Methionine Restrictimentioning
confidence: 99%
“…With reference to the effect of MetR on mtROS generation and oxidative stress, it have been found that 80% MetR (without CR), as well as 40% MetR (Caro et al 2008(Caro et al , 2009, also decreases mtROS generation (mainly at complex I), % free radical leak, mtDNA oxidation, complex I content, specific markers of protein oxidative modification, and membrane unsaturation, in rat heart and liver mitochondria (Sanz et al 2006a, b, c, d), as well as rat kidney and brain mitochondria (Caro et al 2008(Caro et al , 2009, and that these decreases were dose-dependent and stronger at 80% than 40% MetR (Sanz et al 2006a, b, c, d;Caro et al 2008Caro et al , 2009. Strikingly, the pattern of many of these changes was very similar to those previously found in CR and PR.…”
Section: Oxidative Stress and Longevity From The Methionine Restrictimentioning
confidence: 99%
“…[71][72][73] Thus, a decrease in membrane unsaturation, lipid peroxidation and lipoxidation-derived damage has been reported in tissues (liver, heart, and brain) from these dietary restrictions in rats and mice. [74][75][76][77][78][79][80][81][82][83][84] CR has also been shown to reduce levels of lipofuscin in tissues of rodents and C. elegans. [62,[85][86][87][88] From these studies it can be inferred that the magnitude of the change is modest for membrane unsaturation (between 2.5-10%) than that for the lipoxidation-derived molecular damage (between 20-40%) likely due to the added effect of the lower mitochondrial free radical generation also induced by these nutritional interventions.…”
Section: Mechanism Responsible For the Longevity-related Differences mentioning
confidence: 99%
“…The dietary factor that may be responsible for part of the longevity extension effect occurring in chronic ER is the restriction of the specific amino acid methionine. Studies have shown that methionine restriction can decrease mitochondrial ROS production and oxidative stress (Caro et al 2009a). Restriction of dietary amino acids other than methionine decreases mitochondrial protein oxidation and increases SIRT1 in rat liver (Caro et al 2009b).…”
Section: Introductionmentioning
confidence: 99%